Axl Is Essential for in-vitro Angiogenesis Induced by Vitreous From Patients With Proliferative Diabetic Retinopathy - Wu, Wenyi; Xu, Huizuo; Meng, Zhishang; Zhu, Jianxi; Xiong, Siqi; Xia, Xiaobo; Lei, Hetian (Frontiers in Medicine, 2021)
Proliferative diabetic retinopathy (PDR), characterized mainly with abnormal epiretinal angiogenesis forming fibrovascular membranes (FVMs), threatens vision of people with diabetes; FVMs consist of extracellular matrix and a variety of cell types including vascular endothelial cells. Axl, one of receptor tyrosine kinases, can be activated indirectly by vascular endothelial growth factor-A (VEGF-A) via an intracellular route for promoting angiogenesis. In this study, we revealed that growth arrest-specific protein 6 (Gas6), a specific ligand of Axl, was elevated in vitreous from patients with PDR and that Axl was activated in FVMs from patients with PDR. In addition, we demonstrated that in cultured human retinal microvascular endothelial cells (HRECs), Axl inhibition via suppression of Axl expression with Clustered Regularly Interspaced Short Palindromic Repeats/ CRISPR-associated protein 9 or through inactivation with its specific inhibitor R428 blocked PDR vitreous-induced Akt activation and proliferation of HRECs. Furthermore, PDR vitreous-heightened migration and tube formation of HRECs were also blunted by restraining Axl. These results indicate that in the pathogenesis of PDR, Axl can be activated by Gas6 binding directly and by VEGF-A via an intracellular route indirectly, suggesting that Axl plays a pivotal role in the development of PDR and that Axl inhibition shows a bright promise for PDR therapy.